2005
DOI: 10.1007/s10495-005-2217-0
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy-induced death of HCT 116 cells: Apoptosis with or without Bax expression

Abstract: Cell death following photodynamic therapy (PDT) with the photosensitizer Pc 4 involves the intrinsic pathway of apoptosis. To evaluate the importance of Bax in apoptosis after PDT, we compared the PDT responses of Bax-proficient (Bax(+/-)) and Bax knock-out (BaxKO) HCT116 human colon cancer cells. PDT induced a slow apoptotic process in HCT Bax(+/-) cells following a long delay in the activation of Bax and release of cytochrome c from mitochondria. Although cytochrome c was not released from mitochondria follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In an HCT116 Bax knockdown line, apoptosis proceeded without caspase-3 activation, but this phenomenon was also observed in wild-type HCT116. 5 This is not the case with L1210 cells, where procaspase-3 cleavage and DEVDase activation occurs within minutes of photodamage. 7 Irradiation of HeLa cells photosensitizer with hypericin was also found to initiate autophagy, but only if both Bax and Bak were silenced.…”
Section: Quantitation Of Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…In an HCT116 Bax knockdown line, apoptosis proceeded without caspase-3 activation, but this phenomenon was also observed in wild-type HCT116. 5 This is not the case with L1210 cells, where procaspase-3 cleavage and DEVDase activation occurs within minutes of photodamage. 7 Irradiation of HeLa cells photosensitizer with hypericin was also found to initiate autophagy, but only if both Bax and Bak were silenced.…”
Section: Quantitation Of Autophagymentioning
confidence: 99%
“…The responsiveness of the Bax knockdown is consistent with reports by Oleinick's group showing that absence of Bax, or of procaspase-3, did not protect cells from phototoxic effects of PDT using the phthalocyanine photosensitizer Pc 4. [3][4][5][6] Time sequence of autophagy and apoptosis A typical result after exposure of L1210 cells to an LD 90 PDT dose of CPO is shown in Fig. 5.…”
Section: Apoptotic and Cytotoxic Response To Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…The photosensitizer hypericin reportedly detaches hexokinase from mitochondria (Miccoli et al, 1998), whereas the phthalocyanine photosensitizer Pc 4 causes the photochemical destruction of Bcl-2 (Xue et al, 2001). Altogether, available data suggest that photosensitizing agents can target mitochondria, where they induce apoptosis independently from the p53 status, even in Bax-negative cells (Chiu et al, 2005).…”
Section: Chemotherapy and Mitochondriamentioning
confidence: 99%
“…Oleinick's group reported that PDT-induced cell death in the Bax-deficient DU145 prostate cell line 5 and a Bax knock-out HCT116 cells line 17 was neither necrotic nor apoptotic. 5 We found that DU145 cells were killed by PDT protocols employing the ER photosensitizer CPO without development of apoptotic morphological features, loss of mitochondrial potential, formation of condensed nuclear chromatin or the activation of pro-caspases 3/7.…”
mentioning
confidence: 99%